Immunophenotyping - A tool for the differential diagnostics of lymphadenomegaly - Pikalova, Zuzana; Szotkowski, Tomas; Indrak, Karel (Biomedical papers, 2007)
Backround: Flow cytometry is a method that enables the automated quantification of a set of parameters for a large number of cells or cell-like particles. It is also possible to analyze solid tissues after reduction to a single cell suspension. One of the applications of fl ow cytometry is immunophenotyping.Aim: The authors try to introduce the basic physical and biological principles of fl ow-cytometry to the broader public and to prove the benefits of method in lymph nodes assessment.Method: A common method of immunophenotyping with the help of labeled monoclonal antibodies applied to lymph node cells was used.Results: Flow cytometry revealed the infiltration of the extirpated lymph node with leukemic cells.Conclusions: The authors demonstrate fl ow cytometry as a relatively less common but efficient way of lymph node assessment in a patient with an anamnesis of acute lymphoblastic leukemia. They also discuss the contribution of immunophenotyping to the process of the differential diagnostics of lymph nodes enlargement.
Keywords: Flow cytometry/Solid tissue/Immunophenotyping/Acute leukaemia/Lymph nodes